Potential link between periodontal disease and alzheimer’s disease - Abdul Gani Soulissa (Makassar Dental Journal PDGI Makassar, 2018)
Alzheimer’s disease is a progressive generative disease on brain tissues which often found on people above 65 years old. The main etiology of Alzheimer’s disease is unknown; however in people with Alzheimer, it is found excessive protein, fiber and acetylcholine in brain which reduce the number of effective and healthy neuron. There is still lack of research with regards to the relationship between periodontal disease and Alzheimer’s disease, although it is assumed there is a linkage between both, as people with Alzheimer has worse oral hygiene and gingival bleeding. This paper aims to explain the potential link between periodontal disease and Alzheimer’s disease. There is two mechanisms which are assumed to trigger Alzheimer’s disease, namely microgial cell which causes neural damage and Porphyromonas gingivalis invasion on brain. P.gingivalis is periodontal pathogen which able to block immune system in host. P.gingivalis may block immune to form adheren bond with eritrosit which then enters into systemic circulation without identified by immune system and lastly into brain, so that inflammation molecules may penetrate blood-brain barrier into serebral region. TNF-α, which is alleged to be the crucial inflammation mediator causing Alzheimer’s disease also involves in inflammation mechanism. TNF-α may cause demyelination, inflammation, and disorientation of blood-brain barrier, which result in cell death. It was concluded that chronic condition on periodontal disease may enable bacteria to penetrate into blood and cause brain inflammation. Periodontal disease is believed to be a risk factor of Alzheimer’s disease.